Relation Between Encapsulation and Adherence Properties of Bacteria Streptococci of Serological Group B to DEAE-Sephacel (HUBUNGAN ANTARA KEBERADAAN KAPSUL DENGAN SIFAT ADHESIFITAS BAKTERI STREPTOKOKUS GRUP B PADA DEAE-SEPHACEL) - Pasaribu, Fachriyan; Wibawan, I Wayan Teguh; Lammler, Christoph (Jurnal Veteriner; Vol 4 No 1 (2003), 2016)
Abstak dapat dibaca pada Full Text Abstract can be read at Full Text
Keywords: Encapsulation, Adherence Properties, streptococci group B, DEAE-spachel